Analisis Daya Dukung Base dengan Menggunakan Limbah Cangkang, Bottom Ash, dan Fly Ash Berdasarkan Uji CBR Laboratorium - Sinurat, Berkat; Abrar, Aidil; Abdillah, Nuryasin (Sekolah Tinggi Teknologi Dumai, 2024)
One of the contributors to industrial waste in Indonesia is the Palm Oil Shell which produces a large amount of palm oil processing waste, and produces two types of waste, namely light ash (fly ash) and heavy ash (bottom ash). This test is carried out to calculate the amount of bearing capacity that can be received by the base made from waste comparisons, there are 4 comparisons different percentages, namely mixing 55% shell, 10% bottom ash and 35% fly ash, mixing 55% shell, 15% bottom ash and 30% fly ash, mixing 55% shell, 20% bottom ash and 25% fly ash, mixing 55% shell, 25% bottom ash and 20% fly ash. From the test results with different mixtures, the results obtained, that the mixture of 55% shell, 10% bottom ash and 35% fly ash, get the results of the bearing capacity for the base better than the other 3 mixtures, namely, mixing 55% shell, 15% bottom ash and 30% fly ash, mixing 55% shell, 20% bottom ash and 25% fly ash, mixing 55% shell, 25% bottom ash and 20% fly ash. This shows that with the same percentage of shell, the mixture with the addition of more fly ash than bottom ash has a better bearing capacity.